EVALUATION OF THE ADVANTAGES OF USAGE OF CONTAINERS IN HOUSING PRODUCTION IN TERMS OF SUSTAINABILITY - Akar, Ecem; Belek Fialho Teixeira, Müge; Yazıcıoğlu, Deniz Ayşe (Advances in Social Sciences Research Journal, 2017)
Sustainable building construction aims to create a system that provides people with humanely and equitable economic opportunities through the harmony of the built environment with the natural environment. To this end, different approaches are utilized such as re-functioning, use of environmentally friendly methods in production, employment of building items suitable for climate and topography, consideration of energy efficiency in the building life cycle, utilization of renewable energy sources, use of local or traditional materials and minimization of waste generation during construction and destruction process of buildings. One of the most popular approaches among these is the "utilization of containers in the production of sustainable buildings", which is a sub-field of the re-functioning approach. In this context, the objective of this study is to evaluate the advantages of utilization of containers in the production of sustainable buildings through a systematic approach. However, the realization of this assessment within a single study for all building types is quite difficult to achieve as a scientifically significant result. As such, as a methodology, the first stage of the study will determine which structure type should be considered. Subsequently, the criteria to be based on, in the evaluation of the advantages of producing this structure type (containers) in terms of sustainability will be described. At the last stage, certain criterias that the containers should meet in line with the data obtained from the literature will be determined.